Analisis Proses Piercing Pada Pembuatan Produk Joint Brake ROD KTMY Untuk Sepeda Motor Honda di PT. XYZ - Tanjan Mulyana; Oleh Oleh (Peneliti.net, 2022)
This study discusses the analysis of the piercing process in the manufacture of joint brake rod products based on data in the field. The analysis of the piercing process carried out is to maximize the maximum value that must be taken. The purpose of the analysis in this comparison process is to understand the workings and forces required by the stripper plate and those required during the piercing machine capacity process. The research method used is through direct observation of literature studies that have been obtained in the form of books or journals and the internet as references. This calculation is carried out to be used as a benchmark as a comparison material from the calculation results with information data on the number of joint brake rods in the field. This comparison material is based on several basic theories and conclusions obtained from the calculation results. Therefore, the process that occurs in the press machine, especially in the piercing process, there are several things that need to be considered to produce a good and optimal product. From this study it can be concluded that the amount of force required to carry out the piercing process is 13,782,96 N. The force required for the plate stipper to hold the material during the piercing process is 137,829,6 N and the core capacity of the machine determines the amount of emphasis for the production process by adding up all the forces. what happens in the process.